Cross-modal effects of thermal and visual conditions on outdoor thermal and visual comfort perception. (December 2020) - Lam, Cho Kwong Charlie; Yang, Hongyu; Yang, Xia; Liu, Jiarui; Ou, Cuiyun; Cui, Shuhang; Kong, Xiangrui; Hang, Jian
Abstract: People are exposed to multiple stimuli in urban environments, but most studies have investigated the unimodal effect of thermal and visual conditions on human comfort perception. It remains unclear whether the cross-modal effect found in indoor multisensory studies applies to outdoor environments. To understand the cross-modal effect of thermal and visual conditions on outdoor comfort perception, we conducted a thermal comfort survey ( n  = 4304) in Guangzhou and Zhuhai (September 2018). We used the Universal Thermal Climate Index (UTCI) heat stress classification and sky conditions to stratify our results. The thermal sensation vote was positively correlated with sun sensation vote. There was a significant interaction between UTCI heat stress conditions and sunlight preference vote on thermal comfort vote. The sun sensation (brightness) and sunlight preference vote had a cross-modal effect on thermal sensation and thermal comfort vote under various UTCI heat stress conditions. Under extreme heat stress, respondents' thermal sensation did not differ significantly between different sun sensation and sunlight preference groups. Thermal sensation, preference and comfort vote had a cross-modal effect on sun sensation and sunlight preference under different sky conditions. Under partly cloudy conditions, sun sensation did not differ significantly between certain thermal sensation and preference groups. A theoretical framework is provided to explain the cross-modal effect between thermal and visual perception. Our findings suggest outdoor thermal discomfort can be alleviated by improving visual comfort and vice versa. Therefore, urban design should consider the combined effect of visual-thermal stimulants in optimizing overall pedestrian comfort and promoting urban liveability. Highlights: Outdoor thermal sensation is positively correlated with sun sensation. Cross-modal effect exists between outdoor thermal and visual comfort. Significant association is found between thermal perception and sunlight preference. Interaction between UTCI and sunlight preference on thermal comfort is significant. Provide theoretical framework to explain cross-modal effects in comfort perception.